Nutritional requirements for methyl orange decolourisation by freely suspended cells and growing cells of Lactobacillus casei TISTR 1500 - Seesuriyachan P. (2014)
Lactobacillus casei TISTR 1500 possesses cytoplasmic azoreductase and can breakdown azo bonds under microaerophilic condition. It was found previously that a growing culture is more tolerant to a high initial dye concentration than freely suspended cells supplied only with sucrose. The present study is aimed at investigating the nutritive requirements for decolourisation by the growing cells and the freely suspended cells using Plackett-Burmann experimental design. In this study, the composition of the medium was found to play an important role in methyl orange decolourisation and biomass production. Sucrose, meat extract and peptone increased methyl orange decolourisation by freely suspended cells, whereas sodium acetate exerted a negative effect on decolourisation. In addition, it was observed that the yeast and meat extracts enhanced the degradation of the dye by the growing cells. Sucrose was an important factor in biomass production by freely suspended cells and growing cells. On the other hand, dipotassium hydrogen phosphate and sodium acetate decreased the biomass production. These findings promote the understanding and knowledge about the requirements of azo dye decolourisation by Lactobacillus casei. © 2011 by Maejo University, San Sai, Chiang Mai, 50290 Thailand.